2018
DOI: 10.1007/978-3-319-93034-3_22
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning for Forecasting Stock Returns in the Cross-Section

Abstract: Many studies have been undertaken by using machine learning techniques, including neural networks, to predict stock returns. Recently, a method known as deep learning, which achieves high performance mainly in image recognition and speech recognition, has attracted attention in the machine learning field. This paper implements deep learning to predict one-month-ahead stock returns in the cross-section in the Japanese stock market and investigates the performance of the method. Our results show that deep neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 15 publications
1
44
0
Order By: Relevance
“…Their Simulation outcome demonstrated the attractiveness of their proposed ensemble method compared with auto-regressive integrated moving average, generalised autoregressive conditional heteroscedasticity. Likewise, Abe et al [34] applied a deep neural network technique to predict stock price and reported that deep technique is more accurate than shallow neural networks.…”
Section: Related Work Evaluationmentioning
confidence: 99%
“…Their Simulation outcome demonstrated the attractiveness of their proposed ensemble method compared with auto-regressive integrated moving average, generalised autoregressive conditional heteroscedasticity. Likewise, Abe et al [34] applied a deep neural network technique to predict stock price and reported that deep technique is more accurate than shallow neural networks.…”
Section: Related Work Evaluationmentioning
confidence: 99%
“…The hyper-parameters for neural networks are chosen to define one rather shallow (NN1) and one deeper (NN3) network. The structures are comparable to those of Abe and Nakayama (2018) and the orders of magnitude are also similar to those of Gu et al (2018).…”
Section: Boosted Treesmentioning
confidence: 57%
“…The past few years have witnessed a surging number of the applications of deep neural networks (DNNs) for forecasting financial markets. Abe and Nakayama [23] used DNNs to predict one-month-ahead cross-section stock return. Various DNN structures, with differing numbers of layers and differing numbers of neurons in each layer, were investigated.…”
Section: Deep Learning Approachesmentioning
confidence: 99%